Elsewhere. Ontology and ethics between Kafka and Levinas - Labate, Sergio (Itinerari, 2024)
There could be no Burrow if there were no elsewhere. Everything in the burrow starts with life, but life simply isn’t there. The burrow is precisely this: the effort to give a form of space to the life that is elsewhere. As also happens in the house of Levinas: another attempt to give a form of space to the radical separation between ontology and ethics. With a fundamental difference: in Kafka the burrow is formed starting from a primacy of thought, in Levinas starting from the primacy of the sensible.